Penerimaan diri pada remaja pengguna aktif media sosial: Bagaimana kecenderungan Body image? - Permana, Mochammad Titis Titis Indra; ., Herlan Pratikto; Aristawati, Akta Ririn (JIWA: Jurnal Psikologi Indonesia, 2024)
Previous research shows that body image is related to self-acceptance. This research aims to determine the relationship between body image and self-acceptance among teenagers who are active users of social media. This study uses a quantitative approach. The population in this study were teenage students in grades 10, 11 and 12 of SMA 17 August 1945 Surabaya. 332 students. Then the sample was taken using a purposive technique with several categories including active social media users, having 2 different social media accounts, aged 16-18 years. And use social media more than 3 hours a day. while the participants used as research respondents were 181 students using the Slovin formula. The results of data analysis using the Sphearman Rho technique in this study showed a p value of: 0.384 with a significance of 0.001 (p<0.05), which means this study concluded that there was a significant positive correlation between Body Image and self-acceptance. The conclusion that can be drawn from this research shows that there is a significant positive relationship between Body Image and Self-Acceptance of Adolescents who are Active Social Media Users.